Analisis Work Life Balance Terhadap Kinerja Karyawan Di Divisi Purchasing PT X - Harlim, Jeffri Lesmana; Sirait, Tongam (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to examine the effect of work life balance on employee performance in the Purchasing Division of PT X. This study is a quantitative descriptive and associative study. Quantitative research is conducted to measure the relationship between the variables Work life Balance (X) and Employee Performance (Y) using numerical data collected through questionnaires. In this study, the population determined is all employees working in the Purchasing Division of PT X, which is located in Riau Province. This division was chosen because it has a crucial role in the company's operational processes, especially in ensuring the smooth procurement of raw materials, equipment, and services needed to support the company's production and activities as a whole. The sample in this study amounted to 70 employees working in the Purchasing Division of PT X. The sample selection was carried out using a saturated sampling technique, namely a sampling technique in which all members of the population are used as samples because the number is relatively small and can still be reached in this study. The results of a simple linear regression analysis show that Work Life Balance has a positive and significant effect on Employee Performance. With a significance value of 0.045 which is smaller than 0.05, the hypothesis of this study is accepted. In addition, the coefficient of determination (R Square) of 58% indicates that Work Life Balance can explain most of the variation in employee performance. The better the Work Life Balance felt by employees, the higher the performance they achieve. Employees who can balance work and personal life tend to be more productive, have high work motivation, and are able to carry out their duties well.